2021
DOI: 10.1038/s41598-021-97797-0
|View full text |Cite
|
Sign up to set email alerts
|

The virucidal effects of 405 nm visible light on SARS-CoV-2 and influenza A virus

Abstract: The germicidal potential of specific wavelengths within the electromagnetic spectrum is an area of growing interest. While ultra-violet (UV) based technologies have shown satisfactory virucidal potential, the photo-toxicity in humans coupled with UV associated polymer degradation limit their use in occupied spaces. Alternatively, longer wavelengths with less irradiation energy such as visible light (405 nm) have largely been explored in the context of bactericidal and fungicidal applications. Such studies indi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 46 publications
6
36
1
Order By: Relevance
“…Most of the new coronavirus studies do not discuss this possibility. Rathnasinghe et al have mentioned a comparative study with a riboflavin solution but published no results [42].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the new coronavirus studies do not discuss this possibility. Rathnasinghe et al have mentioned a comparative study with a riboflavin solution but published no results [42].…”
Section: Discussionmentioning
confidence: 99%
“…To note, in the context of disinfection and decontamination classical ultraviolet lamps are generally regarded as a highly efficient and wellestablished tool. Nevertheless, these devices possess some nonnegligible limitations such as the inability to penetrate deeply into fluids, the induction of polymer degradation, and the emergence of phototoxic responses in humans [11]. The setting of our experimental model allowed us to overcome the previously described limitations by employing blue LED light.…”
Section: Discussionmentioning
confidence: 99%
“…Another study recently conducted by Rathnasinghe [11] explored the impact of 405 nm light on SARS-CoV-2, obtaining viral inactivation with an irradiance ranging from 0.035 to 0.6 mW/cm 2 . The authors irradiated the virus for 24 h and observed a reduction after at least 4 h of illumination.…”
Section: Discussionmentioning
confidence: 99%
“…Rathnasinghe et al [27] explored the effect of 405 nm light with irradiance from 0.035 to 0.6 mW/cm 2 on SARS-CoV-2, obtaining viral inactivation after at least 4 h of illumination. Although the irradiance was very low from that tested in the current study, and in the other research described above, the total energy reached very high levels.…”
Section: Discussionmentioning
confidence: 99%